The Role of Islamic Religious Education Teacher in Preventing Radicalism in State Junior High Schools - Muhammad Anas Ma'arif; Rusydi, Ibnu; Hali, Ali Usman; Rohmah, Miftakhur (Jurnal Pendidikan Islam Indonesia, 2023)
The purpose of this study was to analyze and describe the role of PAI teachers in preventing radicalism in SMP Negeri 1 Gondang and to analyze and describe the strategies of PAI teachers in preventing radicalism in SMP Negeri 1 Gondang. The approach used in this study is to use a qualitative approach to the type of case study research. Data collection is done by observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and data verification. From the research conducted, it can be concluded as follows: 1). The role of the Islamic Religious Education Teacher in Preventing Radicalism in Gondang 1 Public Middle School, namely, a) The teacher as a motivator for students, b) The teacher as a guide for understanding moral values, c) Doing good habituation by carrying out positive activities, d) Teacher as an evaluator. 2). The strategy for PAI teachers to prevent radicalism in Gondang 1 Public Middle School, namely, a) Through PAI learning in class, b) Through religious and extracurricular activities.